RISE: Clove, habbatus sauda, neem and COVID-19 / Dr Che Puteh Osman and Dr Normala Abd Latip - Osman, Che Puteh; Abd Latip, Normala (Office of the Deputy Vice-Chancellor (Research & Innovation), 2021)
COVID-19 has claimed more than 3.7 million lives, with more than 174 million infections globally when this article is written.